2018
DOI: 10.30910/turkjans.471355
|View full text |Cite
|
Sign up to set email alerts
|

Karasu Nehri’nden (Erzincan) Alınan Su, Sediment ve Capoeta umbla Dokularındaki Ağır Metal Düzeylerinin Belirlenmesi

Abstract: Özet Bu çalışmada, Karasu Nehri'den alınan su ve sediment örneklerinde, ayrıca nehirden yakalanan Capoeta umbla balıklarının karaciğer, solungaç ve kas dokularında bazı ağır metallerin (Alüminyum (Al), Arsenik (As), Krom (Cr), Bakır (Cu), Demir (Fe), Manganez (Mn), Nikel (Ni), Kurşun (Pb) ve Çinko (Zn)) birikim düzeylerinin belirlenmesi amaçlanmıştır. Bu amaçla suyun sıcaklık, pH ve çözünmüş oksijen değerleri ölçülmüştür. Suda yapılan analizler sonucunda en fazla As ölçülürken, Al, Fe, Pb ve Zn metalleri suda … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…Fe and Cd levels were higher than those measured in Lake Hazar (Canpolat 2013) and the Keban Dam Lake (Cağlar et al 2019). Similar results were obtained for tissues of C. umbla in studies conducted in the Tercan Dam Lake (Gunes et al 2019) and the Karasu River (Sokmen et al 2018). Fe values were higher, while Pb values were lower than those obtained by Sonmez et al (2012) for C. umbla from the Karasu River.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Fe and Cd levels were higher than those measured in Lake Hazar (Canpolat 2013) and the Keban Dam Lake (Cağlar et al 2019). Similar results were obtained for tissues of C. umbla in studies conducted in the Tercan Dam Lake (Gunes et al 2019) and the Karasu River (Sokmen et al 2018). Fe values were higher, while Pb values were lower than those obtained by Sonmez et al (2012) for C. umbla from the Karasu River.…”
Section: Discussionsupporting
confidence: 84%
“…Similarly, another study (Eroglu et al 2016) reported that organs tend to accumulate high concentrations of heavy metals as the size of Capoeta trutta increased. Sokmen et al (2018) suggested that, except for a few cases, there was a positive significant correlation between metal concentrations in the muscle tissue and fish size (length and weight) for Capoeta umbla in the Karasu River (Erzincan, Turkey). Another study showed that in most cases there was a positive correlation between fish size (length and weight) and sex.…”
Section: Discussionmentioning
confidence: 99%
“…Aziziye, Çat and Aşkale districts of Erzurum Province are within the boundaries of Karasu Lower Basin. The drainage area of the Karasu River, the most significant tributary of the Euphrates River, in Erzurum is 1642 km 2 and its average flow rate is 4,304 m 3 /sec [20,21]. The research area is approximately 40 km away from the city center of Erzurum.…”
Section: Description Of Study Areamentioning
confidence: 99%
“…Today, one of the most important dangers for all living things in the ecosystem is environmental pollution. Environmental pollution emerged especially with the start of urban life and increased in parallel with the industrial revolution [1,2]. Especially in the century we live in, the industrial, agricultural and social activities of human beings cause the pollution of the environment and the deterioration of the balance of the ecosystem.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the aquatic ecosystem is affected the most from this pollution in our country as in the whole world. Lakes and streams with potable water started to decrease; Many wetlands have been destroyed by pollution [2,3]. Metals, which are densely found in the aquatic ecosystem, cause a wide range of pollution due to their presence in many different substances.…”
Section: Introductionmentioning
confidence: 99%